Barrios Cerrados. As cidades coreografadas de Buenos Aires. Nordelta - João Paulo Castro Tavares Ortigão de Oliveira (2014)
This dissertation is a reflection about closed condominiums, well known as gated communities, urban expression of social polarization, that are dotted throughout the terrestrial sphere. Having the "barrios cerrados" of Buenos Aires as a main reference, this study has the intention to undertake a reflection about the appearance and expansion of these new real estate products that are the combination of two key elements: "community" and "inaccessibility". The evolution of this kind of urbanization has to be analyzed from a political, historical and social perspective as they vary from place to place, and have different origins, localizations and dimensions. The purpose is to study these projects, which resulted from enormous social disparities in extremely fractured societies, by investigating the reasons that led the medium and upper classes to opt for segregation and "self-isolation", according to the thoughts of authors like Harvey, Davis or Viard. The phenomenon of globalization and "culture world" of Gilles Lipovetsky provides the theoretical background, which informs about the social processes of construction of references of "taste", consumption and living types that mark the social distinction, mentioned by Pierre Bourdieu. In the first stage the subject is only cursorily addressed. Having the city of Buenos Aires and the argentinian reality as a reference, one gets to the plenitude of the theme with its materialization through one of the most important condominiums of the city "porteña", seen as a Master Planned Community: Nordelta. Researching its particularities and the dwelling buildings themselves that constitute it, the goal is to establish patterns of "taste" and understand in what way the fear and the inclusion in a "risk society" can contribute to this social isolation. The housing estates illustrate the "taste" of the residents and, at the same time, their position in the extremely fragmented society of Buenos Aires. All these issues have a clear influence on the differentiation in the work that an architect performs and the way they respond to projects according to the variety of social demands. In what way does the architect influence the construction of the city when he answers to the demanding necessities of society and to the new "hypermodern" society? In what way does the creation of patterns of "taste" contribute to social class distinctions and even within the social classes?